Selecting Indicators for Assessing Neighbourhood Sustainability: The Metropolitan Lagos Workflow - Onyango, Vincent; Adewumi, Solomon Ayomikun (European Scientific Journal, ESJ, 2021)
Neighbourhood Sustainability Assessment Frameworks (NSAFs) are increasingly touted as crucial in planning and designing sustainable urban neighbourhoods. Ostensibly, NSAFs ensure that sustainability concerns are duly addressed following the recognition that neighbourhoods are key building blocks of urban areas. While the NSAF discourse has largely involved developed countries, the selection of appropriate indicators to use in an NSAF has remained a problem often because of little robust evidence to support the selected indicators. Also, as develoing countries are largely absent in this discourse, this paper presents an exemplar approach and workflow for selecting NSAF indicators for a Sub-Saharan Africa (SSA) context. Positivist techniques (weighted average, co-efficiency of variation, and content validity in ratio) are used to rank the significance of the stakeholders’ indicated perceptions and preferences collected using questionnaire surveys from metropolitan Lagos. This paper’s significance lies in showcasing the robust methodological approach and sound evidence-base for selecting the indicators based on input form diaparate stakeholders: including data requirements and workflow that SSA countries can easily adopt.